Desain dan Formula Warna dari Bahan Alami Perdesaan dalam Karya Sasirangan Inovatif - Hesty Heryani (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
Sasirangan cloth is one of the traditional handicrafts of South Kalimantan Province, which need to be developed and conserved continuesly. Term of Sasirangan is a combining words form Sa means one, and Sirang which means a cloth made by sewing and binding by hands and then pulling the yarn out. This research was aimed to produce an inovative design of sasirangan by combining several natural dye materials. The method was referred to the production of several unique motifs (Figure 1) and formulation of natural dye materials. Formula I (as a basic motif) consist of Temulawak extract (Curcuma xanthorrhiza) and Teak leaves extract (Tectona grandis) with percentage ratio of 80:20. Formula II was confirmed as a Tabat Barito leaf motif, utilize mango leaves extract (Mangeifera indica), combined with ginger (Zingiber officinale) and temulawak extract with percentage of ratio was 70:20:10 consecutively. Formula III (gigi haruan motif) utilized the mango leaves and ginger extract (80:20). Referring to the HSL color pattern (Hue:Sat:Lum), formula I produced a ivory yellow with HSL number was 42:255:205. Formula II and formula III delivered a young leaf green (64:255:205) and dark green (64:255:46), respectively. In this research we used a silk material. Quality of sasirangan was determined absolutely by the complexity of design, which consist of quality of binding, color formulation, fixation method, optimal soaking time, drying time, and caring of the material.